PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP AUDIT REPORT LAG DENGAN AUDIT TENURE SEBAGAI VARIABEL MODERATING (Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016) - Zulfikar Zulfikar; Nasrizal Nasrizal; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the audit tenure as the moderating influence of firm size and profitability on audit report lag. The population in this research is manufacturing companies listed in Indonesia Stock Exchange periode 2014-2016. The samples used as many as 38 companies by purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis and hypothesis testing, then we got the conclusion that (1) the size of the company's effect on the audit report lag which shows that the bigger the company, the shorter the audit report lag,(2) the profitability on audit report lag reflecting a company that produce a higher profitability level then the audit report lag will be shorter, (3) tenure audit able to moderate (strengthen) the effect of firm size on audit report lag which shows that companies are audited by an auditor to audit the long tenure has a level of audit report lag is low. Completion of the audit will be faster if the auditors audit the audit firm with long tenure at a large company,(4) tenure audit is able to moderate (strengthen) the influence of profitability on audit report lag indicating that the longer the auditor with the company makes auditors better understand the movement of profit ratio of the companyKeywords : Audit Report Lag, Company Size, profitability, and Tenure Audit